Representations for conditional expectations and applications to pricing and hedging of financial products in Lévy and jump-diffusion setting. Issue 2 (4th March 2019) - Daveloose, Catherine; Khedher, Asma; Vanmaele, Michèle
Abstract: In this article, we derive expressions for conditional expectations in terms of regular expectations without conditioning but involving some weights. For this purpose, we apply two approaches: the conditional density method and the Malliavin method. We use these expressions for the numerical estimation of the price of American options and their deltas in a Lévy and jump-diffusion setting. Several examples of applications to financial and energy markets are given including numerical examples.